Optimization of the SARS-CoV-2 ARTIC Network V4 Primers and Whole Genome Sequencing Protocol - Lambisia, Arnold W.; Mohammed, Khadija S.; Makori, Timothy O.; Ndwiga, Leonard; Mburu, Maureen W.; Morobe, John M.; Moraa, Edidah O.; Musyoki, Jennifer; Murunga, Nickson; Mwangi, Jane N.; Nokes, D. James; Agoti, Charles N.; et al. (Frontiers in Medicine, 2022)
Introduction The ARTIC Network’s primer set and amplicon-based protocol is one of the most widely used SARS-CoV-2 sequencing protocol. An update to the V3 primer set was released on 18th June 2021 to address amplicon drop-off observed among the Delta variant of concern. Here, we report on an in-house optimization of a modified version of the ARTIC Network V4 protocol that improves SARS-CoV-2 genome recovery in instances where the original V4 pooling strategy was characterized by amplicon drop-offs. Methods We utilized a matched set of 43 clinical samples and serially diluted positive controls that were amplified by ARTIC V3, V4 and optimized V4 primers and sequenced using GridION from the Oxford Nanopore Technologies’. Results We observed a 0.5% to 46% increase in genome recovery in 67% of the samples when using the original V4 pooling strategy compared to the V3 primers. Amplicon drop-offs at primer positions 23 and 90 were observed for all variants and positive controls. When using the optimised protocol, we observed a 60% improvement in genome recovery across all samples and an increase in the average depth in amplicon 23 and 90. Consequently, ≥95% of the genome was recovered in 72% (n=31) of the samples. However, only 60-70% of the genomes could be recovered in samples that had <28% genome coverage with the ARTIC V3 primers. Conclusion Utilizing the ARTIC V4 primers, while increasing the primer concentrations for amplicons with drop-offs or low average read-depth, greatly improves genome recovery of Alpha, Beta, Delta, Eta and non-VOC/non-VOI SARS-CoV-2 variants.